Outcome of Pulmonary Rehabilitation on Post-Covid Pneumonia Survivors with Residual Lung Fibrosis - Suvedi, Rashmi; Gyawali, Manju; Shahi, Reema; Shrestha, Asmita; Thapa, Anisha; Adhikari, Shradha; Tarmakar, Suraj; Chaudhary, Deepak; Karthak, Ashish; Gurung, Naresh; Shrestha, Sanjeet Krishna (Nepalese Respiratory Journal, 2025)
Background: A significant proportion of COVID-19 survivors develop residual pulmonary fibrosis, leading to persistent dyspnea, reduced exercise capacity, and impaired quality of life. Pulmonary rehabilitation (PR) may help address these sequelae, but evidence remains limited, particularly in low-resource settings.Objective: To evaluate the effect of an 8-week pulmonary rehabilitation program on functional outcomes in post-COVID pneumonia patients with residual lung fibrosis at Nepal Mediciti Hospital.Methods: This prospective cohort study was done from June 2020 to June 2021 and included adult patients with confirmed residual pulmonary fibrosis on imaging after COVID-19 pneumonia. Participants underwent a structured PR program comprising supervised aerobic and resistance training, breathing exercises, and patient education. Functional status was assessed using the 6-Minute Walk Test (6MWT), Modified Medical Research Council (MMRC) dyspnea scale, and ergometer pre- and post-intervention.Results: Participants showed statistically significant improvements in all key outcomes. Mean MRC total score increased from 49.03 to 56.66 (mean difference 7.63, p < 0.001). Mean 6MWT distance improved substantially from 177.6 meters to 276.9 meters (mean difference 99.3 meters, p < 0.001). Significant reductions were observed in perceived fatigue and dyspnea, both at rest and after the 6MWT (p ≤ 0.003 for all Borg scale comparisons). The distribution of improvements varied among individuals, but most showed positive gains. Age showed a slight, non-significant negative correlation with the magnitude of 6MWT improvement.Conclusion: Pulmonary rehabilitation significantly improves functional capacity, dyspnea, and quality of life in patients with post-COVID residual lung fibrosis. These findings highlight the importance of integrating PR into post-COVID care pathways in resource-limited settings like Nepal.